PENGEMBANGAN LKPD DIGITAL BERBASIS PROBLEM BASED LEARNING UNTUK KEMAMPUAN PEMECAHAN MASALAH SISWA SMK NEGERI 2 KOTA BENGKULU - Rusmaini; Kashardi; Fitriani, Apriza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to produce and describe a digital worksheet based on problem-based learning (LKPD) to improve problem-solving skills for vocational high school students. This research is a developmental research using the ADDIE model, which consists of five development stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study were grade XI students of SMK Negeri 2 Bengkulu City. The instruments used were a material and design validation sheet, a practicality questionnaire, a student response questionnaire, and a mathematical literacy test. This study produced a digital worksheet based on problem-based learning (LKPD) that can facilitate problem-solving skills for vocational high school students on the topic of matrix addition and subtraction operations. The quality of the digital worksheet based on problem-based learning using Canva to improve mathematical problem-solving skills on the topic of matrix addition and subtraction operations for grade XI TGG1 was assessed based on the criteria of validity, practicality, and effectiveness. The validity criteria by the expert team were assessed based on the material validation results, with a material validity level of 80% in the valid category, and the design validation results, with a design validity level of 100% in the very valid category. The practicality criteria were assessed based on the teacher's practicality questionnaire, which was 95.24% in the very practical category, and the student's practicality questionnaire during the small group trial, which was 88.89% in the very practical category.